Exposure to an Anonymous Survivor Instagram Account is Linked to Institutional Betrayal Among Campus Sexual Misconduct Survivors - Hannan, Susan M. (Journal of interpersonal violence, 2023)
The main purpose of this study was to examine whether viewing an anonymous survivor social media (Instagram) account was linked to PTSD symptoms and institutional betrayal among campus sexual misconduct survivors. Data were collected from 259 undergraduate students (78.8% female; 79.2% White) who completed an online cross-sectional survey. Results demonstrated that 85 participants (32.8%) endorsed exposure to at least one unwanted sexual experience since coming to college. Of these trauma-exposed participants, 21 (24.7%) reported clinically elevated symptoms of PTSD secondary to the unwanted sexual experience. The average number of instances of institutional betrayal following the sexual trauma was 2.73 (SD = 2.75), and institutional betrayal was positively correlated with PTSD symptoms (r = .29, p = .008). An independent samples t-test showed that trauma-exposed participants who viewed an anonymous survivor Instagram account specific to their college reported higher institutional betrayal compared to trauma-exposed participants who did not view the account (d = 1.55). Furthermore, frequent viewing of the Instagram account (i.e., at least once per week) was associated with the highest reported institutional betrayal (d = .49). Whether or not trauma-exposed participants viewed the Instagram account did not appear to be associated with PTSD symptoms. To the authors’ knowledge, this is the first study to examine the associations among exposure to an anonymous survivor Instagram account, institutional betrayal, and PTSD symptoms. While further research is needed to understand the causal relationship among these variables, these results highlight the continued and urgent need of institutions of higher education to address campus sexual misconduct, in the form of reporting/adjudication processes and robust prevention programming.